FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINDAKAN TIDAK SELAMAT PADA PEKERJA PROYEK KONSTRUKSI GEDUNG PARKIR PT. X DI JAKARTA TAHUN 2021 - Dzikri Tifa Larasati (2022)
Construction work is currently still a contributor to the high number of work accidents in Indonesia. Things that can trigger work accidents are unsafe actions such as smoking while working and not using PPE for PT.X parking building construction project workers. Internal factors (age, years of service, knowledge, fatigue) and external (SHE supervision, safety talk, physical workload) are factors that encourage people to take unsafe actions. The purpose of this study was to analyze factors related to usafe action of the PT.X. parking lot construction project. This research used in quantitative analysis methods with cross-sectional study design and used the chi-square test. The population of the study was 120 workers with a minimum sample of 101 workers and used accidental sampling. The variables studied were internal factors (age, years of service, and knowledge) and external factors (physical workload and supervision). The results were 46.5% of workers who did unsafe actions. The results of analysis showed the knowledge variable (p-value = 0,000; POR= 5,200; 95%CI = 2,154-12,551) and SHE surveillance (p-value = 0.003; POR = 3,792; 95%CI = 1,653-8.697) had significant association with unsafe action. Companies need to increase supervision and make strict policies related to safety morning talks, toolbox meetings, and supervision, then employees are expected to be more compliant with work procedures applicable in the company.